Geopolitical risk, renewable energy transition and policy response: evidence from the BRICS economies - Talent Thebe Zwane; Akindele John Ogunsola (International Journal of Renewable Energy Development, 2026)
This paper empirically examines the dynamic interplay between geopolitical risk, renewable energy transitions, and policy responses within the BRICS (Brazil, Russia, India, China, and South Africa) economies spanning the period from 1990 to 2023, thus addressing the pressing challenge of harmonizing the energy security priorities with the imperative for sustainable economic growth. Employing cross-sectional autoregressive distributed lag and Bayesian structural vector autoregression methodologies for a comprehensive analysis of short-run and long-run dynamics among variables, the findings show a significant negative relationship between geopolitical risks and the adoption and investment in renewable energy sources. Correspondingly, economic policy uncertainties are observed to spur renewable energy consumption under specific economic circumstances characterized by effective policy frameworks; however, policy uncertainties pose a hindrance to renewable energy investment. Furthermore, the study highlights that exchange rate fluctuations have a significant positive impact on renewable investment decisions, whereas demographic pressures stemming from population growth tend to impede energy transition processes. The response strategies to geopolitical shocks underscore the crucial nexus between policy formulation and stability, which collectively mold energy-related outcomes. The central policy recommendation emanating from this study emphasizes the significance of concerted cooperation among the BRICS nations, including measures such as shared supply-chain assurances, regional financing mechanisms, and harmonized regulatory regimes to alleviate barriers associated with geopolitical risks in the transition to renewable energy sources. Finally, the direct applicability of the results pertains to the unique context of the BRICS bloc, which is due to their specific trade dynamics, technological dependencies, and exposure to commodities.